2021
DOI: 10.1039/d1ta03379d
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling two-phase transport in porous transport layer materials for polymer electrolyte water electrolysis

Abstract: In polymer electrolyte water electrolysis (PEWE), reducing mass-transport losses is crucial for lowering both PEWE capital and operational costs, allowing the widespread commercialization of the technology. In this work, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…In this scenario, it is essential to utilize the available catalyst as efficiently as possible. Recent studies have shown that the structure of the PTL can have an essential impact on CL utilization. Several studies have investigated the bulk properties of the PTL and the respective fluidic transport during operation. A significant influence affecting CL utilization is related to the surface properties of the PTL rather than the bulk features. ,, This is linked to two main reasons: (i) the poor electronic in-plane (IP) conductivity of typical CLs, caused by the disruption of the electronic percolation network of the CL structure and (ii) the in-plane mass transport limitation in the porous structure of the CL under the contact points between PTL and CL.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, it is essential to utilize the available catalyst as efficiently as possible. Recent studies have shown that the structure of the PTL can have an essential impact on CL utilization. Several studies have investigated the bulk properties of the PTL and the respective fluidic transport during operation. A significant influence affecting CL utilization is related to the surface properties of the PTL rather than the bulk features. ,, This is linked to two main reasons: (i) the poor electronic in-plane (IP) conductivity of typical CLs, caused by the disruption of the electronic percolation network of the CL structure and (ii) the in-plane mass transport limitation in the porous structure of the CL under the contact points between PTL and CL.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of anodic CL microstructure analysis lies in the difficulties of achieving high-quality 3D reconstructions, considering the small feature size (< 1 µm 6 ). While three-dimensional reconstructions of PTLs can be easily found in literature for both ex situ 3,7 and operando studies 8 , only one recent publication can be found where a PEWE CL reconstruction was obtained 6 . In 6 , the authors used focused ion beam-scanning electron microscopy (FIB-SEM) to reconstruct a CL employing an unsupported Ir-Ru catalyst.…”
mentioning
confidence: 99%
“…In 2022, Kulkarni et al 9 utilized X-ray micro-CT and investigated the oxygen content distribution with different catalyst loadings. De Angelis et al 47 in 2021 unraveled two-phase (water/oxygen) transport via X-ray micro-CT, figuring out four different connection types of oxygen clusters and how isotropic/anisotropic microstructure could influence the electrolysis performance. One more imaging research interest is to distinguish electrode components within assemblies, which may require combination of Xray CT and other imaging characterization techniques such as ptychography and fluorescence.…”
Section: Why We Need X-ray Ct In Electrocatalysismentioning
confidence: 99%
“…This enables the identification of water saturation in the anode of water electrolyzers, as has been shown in previous studies. 47 Traditionally, neutron imaging has been limited to 2D radiography in the in-plane or through-plane direction of the membrane electrode assembly, owing to low resolution (>5 μm) and long exposure times. However, recent advances in imaging resolution 89 and time scale 90 have enabled the accomplishment of 3D neutron tomography.…”
Section: Iibii X-ray Ct With Neutron Ctmentioning
confidence: 99%
See 1 more Smart Citation